Pengembangan Aplikasi Alat Kesehatan Menggunakan Teknologi Realitas Tertambah Berbasis Android(Studi Kasus: Farouk Farisi Medika) - Eko Purnomo; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to create an application of medical medical devices in which medical device sales can offer its products using Android based Augmented Reality technology. Augmented Reality is a view directly or indirectly of physical objects by adding information then can be displayed in three dimensions (3D). The method used in development uses the Multimedia Development Life Cycle (MDLC). This application development uses the Unity application with the C # programming language. Based on the results of testing on the BlackBox Testing, and testing on smartphones, it can be concluded that this application can run well and all buttons on the application can run according to their function.